ELASTISITAS HARGA TELUR TERHADAP MINAT PETERNAK AYAM PETELUR DALAM MENGEMBANGKAN USAHA PETERNAKANNYA (Studi Kasus Di Desa Sukolilo Kecamatan Wajak Kabupaten Malang) - Anna Lidiyawati (AVES: Jurnal Ilmu Peternakan, 2018)
This research was conducted to layer farmers in Sukolilo village, Wajak in Malang distric .The data collection was conducted during Desember 2017 -“ January 2018 that focus on elasticity of egg price to farmer interest of develop their farming. Research method used is a method of survey sample with determination of the sampling method purposively namely layer chicken farmers who had 300-3000 chickens. The number of the overall sample can be reserach used is egg price, number of the population, feed price, pullet price, afkhir of layer price. Data analysis conducted includes data qualitative and analysis to calculate the elasticity of egg price by used Cobb-Douglas regression analysis. Data prosesscing from the result of this research condusted using the the SPSS version 16,0. The result show that afkhir of layer price have significant to affect elastic of egg price. The research concluded that 1) afkhir of layer price is a factor have significant affect to farmer interest of develop their farming and elastic to egg price 2) number of population, feed price and pullet price are the factors that are not elastic to egg price.Keywods : elasticity of egg price, number of population, feed price, pullet price, afkhir of layer price